Cryptographic construction using coupled map lattice as a diffusion model to enhanced security. (June 2019) - Kumar, Subodh; Kumar, Rajendra; Kumar, Sushil; Kumar, Sunil
Abstract: In this study, a new color image encryption model that uses an intertwining logistic map based confusion mechanism and coupled map lattice based diffusion process. It incorporates mixing based on pseudo random number generator to ensure shuffling incase of same pixels, intertwining logistic map based confusion mechanism enhance the key sensitivity in the model. Finally, Couple map lattice based diffusion is utilized in the model to change the pixels in a way that even one-bit change in a pixel of plain image leads to a change in large number of pixels of the cipher image. The proposed encryption method enhance the security and results in better Number of pixel change rate (NPCR) and Unified average change intensity (UACI) scores. The correlation among the pixels of cipher image is reduced to be negligible. Corresponding results suggest that the proposed model is highly secure as compared with chaos based algorithms for image encryption application.